Pendampingan mahasiswa Kukerta terkait kegiatan desa bersama Ibu PKK Desa Tanjung Pauh dalam pemberdayaan sumber daya alam desa - Muhamad Iqbal; Indra Lesmana; Shyfa Reyhana Kurnia; Baihaqqi Daffa Attoriq; Putri Yani Purnamasari; Melly Risfani; Aulia Agus Anindita; Annisa Azzahra; Mohammat Rizki Mahendra; Zulfa Maharani; Riski Fernando Telaumbanua (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to provide knowledge and skills related to activities where the process in which utilizes the potential of the village which is managed together with PKK women, PKK women try to be able to preserve the village potential so that it is well managed and has a good impact. to the village community. This happened with a program designed by PKK women who were accompanied by students of Kukerta University of Riau. The Real Work Lecture Service Method in Tanjung Pauh Village carried out by Riau University Students in 2022 was carried out using a qualitative method. This method is carried out by means of counseling, observation, participating in the manufacture and documentation. The research resulted in several activities, which became important points related to the purpose of their implementation, which resulted in elements of usefulness, empowerment, intelligence, religion, and unity which were colored by working hand in hand in the essence of the principle of mutual cooperation. In carrying out these activities, the performance evaluation method is also used which is useful as a benchmark for achieving expectations and improving the quality of teamwork to achieve goals and expectations in the implementation of activities with the theme of social service, of course that is the main point obtained by Kukerta students as a forum or means for adapt and establish cohesiveness that is shaded by a series of activity processes.